Post‐acute care use after major head and neck oncologic surgery with microvascular reconstruction. (30th March 2018) - Parhar, Harman S.; Chang, Brent A.; Durham, J. Scott; Anderson, Donald W.; Hayden, Richard E.; Prisman, Eitan
Abstract : Objectives: Post‐acute care (PAC) centers, such as skilled nursing facilities, unskilled nursing facilities, lower acuity hospitals, and rehabilitation centers, serve to optimize recovery after acute care hospitalization. We aimed to identify factors associated with PAC utilization among patients undergoing head and neck cancer surgery with microvascular reconstruction because it may be helpful for patient decision making, discharge planning, and resource allocation. Methods: Retrospective linked analysis of the 2011 to 2015 National Surgical Quality Improvement Program. Eligible patients were identified and stratified by discharge disposition (home or PAC) after their postoperative acute‐care hospitalization. After an initial univariate screen of demographic and clinical variables, a multivariable logistic regression analysis was performed modelling discharge to PAC. Results: Of the 1, 652 identified patients, 261 (15.8%) were discharged to PAC. Those admitted to PAC were older, had a higher burden of comorbidity, and were more likely to be functionally dependent. They also had longer surgeries, longer hospitalizations, higher rates of reoperation, and higher rates of postoperative complications. After multivariate analysis, factors independently associated with PAC discharge included increasing age (odds ratio [OR] 2.12 per 10‐year increase; 95% confidence interval [CI], 1.81–2.48), active smoking status (odds ratio (OR) 1.61; 95% confidence interval (CI), 1.13–2.29), prolonged hospitalization (OR 1.04; 95% CI, 1.02–1.07), and postoperative pulmonary complications (OR 2.02; 95% CI, 1.36–2.99). Conclusion: Of the patients undergoing surgery for head and neck cancers with microvascular reconstruction, 15.8% are discharged to PAC. Age, active smoking status, prolonged hospitalization, and postoperative pulmonary complications (vs. comorbidity, functional status, or primary tumor site) are independently associated with discharge to PAC. Level of Evidence: Level 2c. Laryngoscope, 2532–2538, 2018